Harnessing nitrate over ammonium to sustain soil health during monocropping - Zhu, Linxing; Liang, Aichen; Wang, Rongfeng; Shi, Yaman; Li, Jia; Wang, RuiRui; Wang, Min; Guo, Shiwei (Frontiers in Plant Science, 2023)
In achieving food security and sustainable agricultural development, improving and maintaining soil health is considered as a key driving factor. The improvement based on different forms of nitrogen fertilization has aroused great public interest in improving and restoring monocropping obstacles for specific soil problems. For this, a short-term cucumber cropping field experiment was conducted in the subtropical region of China under four fertilization treatments: ammonium (AN), nitrate (NN), ammonium with dicyandiamide (AN+DCD), nitrate with dicyandiamide (NN+DCD). In this study, we measured the effects of nitrogen forms addition on plant productivity and soil health in a monocropping system over seven seasons. To systematically evaluate soil health, a wide range of soil environmental factors were measured and incorporated into the soil health index (SHI) by entropy method. Compared with ammonium treatment (SHIAN = 0.059, SHIAN+DCD = 0.081), the positive effect of nitrate was mainly reflected in improving soil health (SHINN = 0.097, SHINN+DCD = 0.094), which was positively correlated with the increase in plant productivity of cucumber after seven seasons of monocropping. The most critical factor affecting SHI is soil ammonium nitrogen content, which was negatively correlated with plant productivity. Nitrate promotes soil health and plant productivity by optimizing soil environmental factors. The study thus emphasized the necessity of nitrate input for the sustenance of soil-crop ecosystems, with the consequent possibility of application of the results in planning monoculture obstacle 2 prevention and management measures.